EKSISTENSI MASJID DALAM DIALEKTIKA PUSAT PENGEMBANGAN MASYARAKAT DAN KAWASAN NIAGA: STUDI DI MASJID MUTTAQIEN YOGYAKARTA - Adi Saputro (The Indonesian Journal of Public Administration (IJPA), 2017)
Abstract: Mosque is an integral part of Muslim spiritual, sosial and cultural life. But nowadays the mosque is facing the role and function narrowing from a community development center to a commercial area complement. Therefore, this study aims to determine, describe and analyze the Muttaqien Mosque existence in the dialectic of community development center and commercial area, including education, health, economic and socio-cultural affairs. The research results showed that in education aspect, there are studies which conducted regularly every day to enhance the knowledge and scientific treasures of congregation. In economic aspect, mosque was successful to increase congregation welfare including trader, labor hand, even paddle rickshaws and scholarships for underprivileged children. For health aspect, mosque provides friend space to mothers and children for help the congregate to obtain information on health and nutritional needs of children. And in socio-cultural aspect, mosque contributes in helping the public agenda like mass circumcision and humanitarian assistance when disaster occurs. Keywords: Mosque Existence, Community Development Center, Commercial Area Abstrak: Masjid merupakan bagian integral kehidupan spritual, sosial dan kultural umat Islam. Namun dewasa ini keberadaan masjid semakin mengalami penyempitan peran dan fungsi dari pusat pengembangan masyarakat menjadi sekedar pelengkap kawasan niaga. Penelitian ini bertujuan untuk mengetahui, mendeskripsikan dan menganalisis eksistensi Masjid Muttaqien dalam dialektika pusat pengembangan masyarakat dan kawasan niaga meliputi bidang pendidikan, kesehatan, ekonomi dan sosio kultural. Hasil penelitian menunjukkan bahwa dalam aspek pendidikan, terdapat kajian dan pengajian rutin harian untuk menambah wawasan serta khazanah keilmuan jamaah. Dalam aspek ekonomi, masjid berhasil meningkatkan kesejahteraan jamaah meliputi pedagang, buruh gendong, bahkan pengayuh becak serta memberi beasiswa untuk anak-anak kurang mampu. Di aspek kesehatan, masjid menyediakan ruang sahabat ibu dan anak guna membantu jamaah memperoleh informasi kesehatan dan kebutuhan gizi anak. Dan di aspek sosio kultural, masjid membantu berbagai agenda masyarakat seperti khitanan massal dan bantuan kemanusiaan saat terjadi bencana. Kata kunci: Eksistensi Masjid, Pengembangan Masyarakat, Kawasan Niaga